A Review on Provisioning Quality of Service of Wireless Telemedicine for E-Health Services - -, Mustafa Almahdi Algaet; Muhamad Noh, Zul Azri; Shibghatullah, Abdul Samad; -, Aouache Mustapha; -, Ali Ahmad Milad (IDOSI, 2014)
In general, on-line medical consultation reduces time required for medical consultation induces improvement in the quality and efficiency of healthcare services. All major types of current e-health applications such as ECG, X-ray, video, diagnosis images and other common applications have been included in the scope of the study. In addition, the provision of Quality of Service (QoS) for the application of specific healthcare services in e-health, the scheme of priority for e-health services and the support of QoS in wireless networks and techniques or methods for IEEE 802.11 to guarantee the provision of QoS has also been assessed. In e-health, medical services in remote locations such as rural healthcare centers, ambulances, ships as well as home healthcare services can be supported through the applications of e-health services such as medical databases, electronic health records and the routing of text, audio, video and images. Given this, an adaptive resource allocation for a wireless network with multiple service types and multiple priorities have been proposed. For the provision of an acceptable QoS level to users of e-health services, prioritization is an important criterion in a multi-traffic network. The requirement for QoS provisioning in wireless broadband medical networks have paved the pathway for bandwidth requirements and the real-time or live transmission of medical applications. From the study, good performance of the proposed scheme has been validated by the results obtained. The proposed wireless network is capable of handling medical applications for both normal and life-threatening conditions as characterized by the level of emergencies. In addition, the bandwidth allocation and admission control algorithm for IEEE 802.16- based design specifically for wireless telemedicine/e-health services have also been presented in the study. It has been concluded that under busy traffic conditions, the proposed architecture can used as a feasible and reliable infrastructure network for telemedicine.